Functional roles of CD26/DPP4 in bleomycin‐induced pulmonary fibrosis. Issue 6 (22nd March 2023) - Koyanagi, Yu; Kawasaki, Takeshi; Kasuya, Yoshitoshi; Hatano, Ryo; Sato, Shun; Takahashi, Yukiko; Ohnuma, Kei; Morimoto, Chikao; Dudek, Steven M.; Tatsumi, Koichiro; Suzuki, Takuji
Abstract: The pathogenesis of pulmonary fibrosis involves complex interplay between cell types and signaling pathways. Recurrent alveolar epithelial injury can occur during pulmonary inflammation, causing dysregulation of epithelial repair. Dysregulated repair interacts with mesenchymal, inflammatory, and endothelial cells to trigger fibroblast‐to‐myofibroblast activation. CD26/dipeptidyl peptidase‐4 (DPP4) is a type II membrane protein mediating pleiotropic effect. However, the mechanistic role of CD26/DPP4 in pulmonary fibrosis remains unclear. In this study, we aimed to characterize Dpp4 deficiency in a mouse bleomycin (BLM)‐induced pulmonary fibrosis model and in cell culture systems of human lung fibroblasts (HLFs). Dpp4 knockout ( Dpp4 KO) mouse lungs exhibited lower Ashcroft scale indices, collagen content, and numbers of fibroblasts and myofibroblasts compared with those in C57BL/6 wild‐type (WT) mice. Upregulation of Tgfb1 and Tgfb2 mRNA levels in the lungs after BLM treatment was lower in Dpp4 KO mice compared with those in WT mice. Although TGF‐β‐driven endothelial‐to‐mesenchymal transition (EndMT) has been implicated as one of the mechanisms of pulmonary fibrosis, a number of partial EndMT cells in lungs did not differ between Dpp4 KO mice and WT mice. The proliferation capacity and mRNA levels of COL1A1, a collagen deposition‐related gene, in cultured HLFs were suppressed in DPP4 small interfering RNA‐treated cells. This study indicates that the genetic deficiency of DPP4 has protective effects against BLM‐induced pulmonary fibrosis, partly through the reduction in TGF‐β expression and inhibition of fibroblast activation in the lung. Our study suggests that CD26/DPP4 inhibition is a potential therapeutic strategy for pulmonary fibrosis. Abstract : This current study has advanced our understanding of the functional role of CD26/DPP4 by demonstrating that CD26/DPP4 deficiency attenuates BLM‐induced pulmonary fibrosis in mice through a reduction in TGF‐β expression and inhibition of lung fibroblast activation.